A comparative analysis of a TiO2 nanoparticle dispersion in various biological extracts. Issue 79 (28th August 2015) - Yadav, Tushar; Mungray, Alka A.; Mungray, Arvind K.
<x xml:space="preserve">Abstract</x> Chemical surfactants are used for efficient dispersion of nanoparticles (NPs) but they also cause a hazard to the environment.